Applying Transparency Principle on the Planning and Budgeting in Mataram - Hendriadi Hendriadi; Sahri Sahri; Prayitno Basuki (Universitas Negeri Malang, 2017)
This study aims to discover how far the transparency principle applied in planning and conducting matters in Mataram. A qualitative approach with phenomenology design is used in this study. The data were collected by interviewing 10 people who were selected purposively, completed with observation and documented study, and the data were analyzed with interactive data analysis. The result shows that in the planning, the majority of process and stages in the application, accessibility, and availability of documents, adequacy and completeness of information, the regulation guarantying transparency and information service institution have applied transparency principle; however, the application is not yet adequate because the planning in sphere, the publication process and planning result, as well as the functionality of the Information and Documentation Management Officials (IDMO) are not applied well. Meanwhile, regarding the budgeting, in the planning, the majority of processes, accessibility and availability of documents, adequacy and completeness of information, as well as the information service institution have not yet to apply transparency principle since the budgeting discussion in a Regional House of Representative (RHR) is awfully inaccessible, have excluded the society, have no public socialization and consultation for the Draft of Budget Revenue and Expenditure/Regional Budget, and the IDMO is not yet formed in the Agency of Regional Development Field and in the Agency of Regional Finance.Keywords: Transparency, Information, Planning, and BudgetingJEL Classification: G31, H73